Teaching Poetry: Impact of Teacher’s Non-Verbal Communication on Students’ Learning Outcomes - Naeem Butt, Muhammad; Shafiq, Muhammad (The Journal of Humanities & Social Sciences, 2022)
This experimental study considers the impact of non-verbal communication on the learning achievement of students of class 10th. This study highlights the importance of non-verbal communication in teaching of poetry in the subject of English. The study discusses the research questions of how teacher’s notion of medium of instruction might enhance the teaching of English poetry and what type of learning is possible with the incorporation of prosodic features? Population of the study comprises the selected school in urban area of Peshawar (North-West of Pakistan). Experiment in the actual classroom setting was conducted in the sampled school. The significant difference between pre-and post-tests of the control and experimental groups was tested through paired t-test. Results revealed that teachers created active learning environment through their non-verbal gestures; whereby students were attentive in the classrooms and actively participated in the learning process, which consequently enhanced the level of their retention and understanding. Use of non-verbal communication helped the teacher to provide better understanding to the students in their learning achievement. On the contrary teacher who did not use non-verbal communication in the classroom could not motivate the students for effective learning.